Understanding behavioral intention to subscribe video-on-demand platform during COVID-19 pandemic: evidence from Indonesia - Kania, Rafiati; Ramadhani, Nabila Shafira; Wibisono, Nono; Gunawan, Arie Indra (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2022)
Subscriber-based Video on Demand (SVoD) is currently growing business sector during the COVID-19 pandemic. Since the pandemic effect human mobilization, the Indonesian government strictly regulated visiting the cinema to press Covid-19 outbreak. Consequently, film providers and consumers adopt SVoD as an alternative digital platform. Nevertheless, Indonesian subscriptions are currently lagging behind other countries. In addition, a survey from Coalition Against Piracy in 2019 has discovered that 63 % of Indonesian consumers opt to access illegal streaming services instead of paying subscription fees to video streaming providers. This research empirically examines social influence, perceived risk, hedonic motivation, and utility value to influence behavioral intention to understand what factors influence paying subscriptions. The hypotheses proposed in our research model are tested on a sample of 291 Indonesian subscribers of SVoD platforms. The partial-least square modeling result shows that social influence, hedonic motivation, and utilitarian value can, directly and indirectly, influence behavioral intention. Contrary to research hypotheses, the perceived risk of adopting illegal streaming videos can only indirectly influence behavioral intention. Finally, it is noted that a combination of external and internal consumer motivation will impact subscriptions intention.